PENGARUH KEPEMILIKAN INSTITUSIONAL, KEPEMILIKAN PUBLIK, PERTUMBUHAN PERUSAHAAN DAN TIPE INDUSTRI TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY PADA PERUSAHAAN HIGH PROFILEDI BURSA EFEK INDONESIA - Saputra, Syailendra Eka (RC-INSTITUT, 2019)
This study aims to determine the role of institutional ownership and public ownership to encourage disclosure of corporate social responsibility in high profile companies in Indonesia, in addition this study also aims to prove the influence of company growth and industry type on the amount of disclosure of corporate social responsibility, especially in high profile companies Indonesia. The analytical method used is using panel data regression analysis. The test results show that institutional ownership does not affect CSR disclosure in High profile companies on the Indonesia Stock Exchange, while public ownership, company growth and industry type have a positive effect on CSR disclosure in High profile companies on the Indonesia Stock Exchange.